Experimental seismic behaviors of different connections to CFST end-columns in shear walls. (September 2022) - Yu, Yujie; Luo, Yongqi; Lin, Siwen; Wei, Biao; Jiang, Lizhong; Liu, Qingzhi
Abstract: A new hot-rolled T-shaped connector (HTC) connection was proposed herein to solve the connecting difficulties between H-shaped beams and small-sized composite walls or CFST columns in steel residential buildings. The connection utilizes the hot rolled flange-to-web arch transition in hot rolled beams as the beam-end connector. In this way, the hot-rolled arch transition of the connector provides a smooth section transition at the column face junction to avoid stress concentrations and premature fracture problems in traditional welded junctions. The new connections, together with the existing endplate type and side plate type connections, were applied to a specially-shaped corrugated plate shear wall system. Seismic loading tests were performed to explore seismic behaviors and the applicability of those connections in steel residential buildings. Results indicated that the side plate connections and HTC connections exerted good hysteretic performance with stable hysteretic behaviors, slow stiffness degradation, good energy dissipation ability, and satisfactory ductility. The endplate connection experienced early fracture failure of the side plate to endplate welds. In addition to the satisfactory seismic performance, the proposed HTC connections had no extended stiffeners and little intrusion into the indoor space, and could be easily hidden within partition walls. Highlights: A new hot-rolled T-shaped connector connection was proposed. The applicability of HTC connections in steel residential building systems were investigated. The side plate connection and the new HTC connection possessed good seismic performance. The hot-rolled arch transition provided a smooth stress flow at the column face junction. The HTC connections had convenient fabrication and architectural advantages.